PENGARUH KOMBINASI NUTRISI AB MIX DAN PAITAN (Tithoniadiversifolia (Hemsl.) A. Gray) TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PAKCOY (Brassicarapa L.) DENGAN SISTEM HIDROPONIK - Gianka Pratama Harsan; Fetmi Silvina; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
This study wasaimedtoproducePakcoy (Brassicarapa L.) withbettergrowthandproductionusingHydroponicsystembyapplyingcombinationofNutrients AB MixandPaitan (Tithoniadiversifolia (Hemsl.) A. Gray). The research has beenimplementedfrom November 2020 toDecember 2020 at a screenhouseofTechnicalImplementation Unit (UPT), FacultyofAgriculture, Universityof Riau. The researchwasconductedusing a completelyrandomizeddesign (CRD) consistingof 5 treatments. thetreatmentgivenwas a combinationof AB mix nutritionandfermented paitan. The treatments in this study were AB mix 10 ml.l-1 + POC 0 ml.l-1, AB mix 7,5 ml.l-1 + POC 50 ml.l-1, AB mix 5 ml.l-1 + POC 100 ml.l-1, AB mix 2,5 ml.l-1 + POC 150 ml.l-1, AB mix 0 ml.l-1 + POC 200 ml.l-1 andeachtreatmentwasrepeated 4 times. The observedvariablesconsistedofplantheight, leafwidth, numberofleaves, plantfreshweight, ediblefreshweightandroot volume. The data obtained were analyzedof varian andfurthertestedbyusingDuncan'smultipledistancetestat a level of 5%. The resultsshowedthattheuseof 10 ml.l-1 AB mix wasthebesttreatmentwhichgavesignificantlydifferentresultstoothertreatments and produce 43,75 g of edible fresh weight. Keywords: Hydroponics, Paitan, Fermented Liquid Nutrient, Pakcoy